Pendekatan Games Dalam Meningkatkan Motivasi Belajar Siswa Bagi Relawan Gemma Insani Indonesia - Tita Puspitasari; Dwinesa Anggraeni (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
The aim of this workshop is to become Gemma Insani volunteers have got the ability of classroom management and basic knowlegde about education psychology is related how the way to give the students motivate by using games in learning process. The event is followed by 25 volunteers Gemma Insani Depok. The methods are used in the workshop such presentation, discussion and question and answer, and simulation from the volunteers. The result of the workshop are (1) to train the volunteers’ teaching ability who have got different education background. In application kinds of games that used for all subjects in education level. This event can help hopefully to motivate the students in learning. (2) to use kind of methods in learning process so the student will not feel bored, and (3) be able to have creative thinking in creating or making games based on student- education level.